2016
DOI: 10.15406/mojfpt.2016.02.00042
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Qualities of Dough from Mixture of Flour and Wheat Bran and Possible Correlation between Bra Bender and Mixolab Chopin Equipments

Abstract: The rheological qualities of dough are determined during the mixing, extension and warming of the dough and they are closely correlated with the quality of the flour, however by increasing the amount of the dietary fibers, the qualities change, given that this leads to weakening of the proteins, respectively to the deterioration of gluten net. The equipment which is used in determining the rheological qualities is those of Bra bender: Farinograph, Extensograph, however, lately one also started to use Mixolab C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Rheological properties of dough are closely related to the quality of food made with wheat flour. Rheological properties obtained from Chopin Mixolab are positively correlated with those obtained from Brabender Farinograph [34]. Therefore, rheological qualities determined by Chopin Mixolab can reflect the quality of wheat flour very well.…”
Section: Resultsmentioning
confidence: 99%
“…Rheological properties of dough are closely related to the quality of food made with wheat flour. Rheological properties obtained from Chopin Mixolab are positively correlated with those obtained from Brabender Farinograph [34]. Therefore, rheological qualities determined by Chopin Mixolab can reflect the quality of wheat flour very well.…”
Section: Resultsmentioning
confidence: 99%
“…Significant correlation of wet and dry gluten was recorded with water absorption and dough stability during study on quality of wheat flour [24]. In a study significant correlation was determined between dough development and dough stability time; whereas mixing tolerance index indicated significantly negative correlation [25]. Research findings revealed that dough development time significantly decreased and dough stability time significantly increased by reducing particles size of wheat flour [26].…”
Section: Physicochemical Propertiesmentioning
confidence: 88%
“…The DDT reduced significantly (p< 0.05) on addition of more than 20 % cassava flour. Xhabiri et al (2016) reported increased dough development time of wheat flour with the addition of wheat bran.…”
Section: Mixolab Properties Of Wheat-cassava Composite Flourmentioning
confidence: 99%
“…Increase in WAC may be due to the high amount of starch (broken starch) and fibre in cassava flour (Kumar et al, 2015;Manano et al, 2017;Khan et al, 2019). Xhabiri et al (2016) reported increased water absorption of wheat flour with the addition of wheat bran to the flour which increased the amount of fibre in the composite dough. Dough development time (DDT) of pure wheat flour was low (1.46 min), signifying a weak flour (Dhaka et al, 2012;Dhaka and Khatkar, 2013).…”
Section: Mixolab Properties Of Wheat-cassava Composite Flourmentioning
confidence: 99%
See 1 more Smart Citation